4.6-GHz LHCD Launcher System of Experimental Advanced Superconducting Tokamak. (2nd January 2019) - Liu, L.; Liu, F. K.; Jia, H.; Zhu, W. H.; Zhao, L. M.; Wang, X. J.; Shan, J. F.; Ding, B. J.; Li, M. H.; Yang, Y.; Feng, J. Q.; Wu, Z. G.; et al.
Abstract: A new 4.6-GHz lower hybrid (LH) current drive (CD) (LHCD) launcher has been successfully developed in the Experimental Advanced Superconducting Tokamak (EAST) to achieve long-pulse high-performance plasma. It is capable of coupling up to 6 MW of LH power into the plasma with a parallel index N// from 1.79 to 2.23. Before manufacturing the launcher, key component mock-ups were fabricated and tested to validate the radio-frequency (RF) design and the process feasibility. Test results show good agreement with the design value. So far, up to 3.5 MW of net LHCD power was injected into the plasma, and long-pulse operation capability has been demonstrated: 1.26 MW and 100.4 s, suggesting that the new launcher can effectively couple the microwave energy into plasma, to drive current and extend the high-performance plasma. In this paper, some of the RF design, construction, testing, and recent experimental results of the new launcher are presented.